Serbia and Montenegro : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues and Statistical Appendix paper examines the scope for improving the effectiveness of fiscal policy of Serbia and Montenegro in containing the persistently large external imbalance. The paper discusses the causes of the current problems and presents preliminary results of the projected finances of the Fund for Employees (FE). It suggests options for reducing the cost of pension outlays, and provides preliminary estimates of the impact of the authorities' recent reform package on the FE finances. The paper also provides a description of the main parameters of the Serbian pension system.